MOTHER'S KNOWLEDGE ABOUT LACTATION MANAGEMENT IN PANDAU JAYA VILLAGE, SIAK HULU DISTRICT, RIAU PROVINCE - Pinondang Hotria Siregar; Putri Wulandini S (LPPM Universitas Abdurrab, 2023)
Exclusive breastfeeding can be hampered by several things, such as low knowledge of mothers and families regarding the benefits of breast milk, the correct way to breastfeed, lack of lactation counseling services, socio-cultural factors, incessant marketing of formula milk, lack of support from health workers. This research aims to determine mothers' knowledge about lactation management in Panda Jaya Village, Siak Hulu Regency, Riau Province. This research design uses a descriptive type of research with a cross sectional research design. The population in this study were mothers who had babies aged 6-24 months. The sample in this study consisted of 60 respondents. Data collection using questionnaires. The research results showed that the most knowledge was in the sufficient category with 42 respondents (75%), and sufficient knowledge with non-exclusive provision was 8 respondents (13.3%). It is recommended that community health centers and health workers expand health promotion targets related to lactation management with breastfeeding.